Youth empowerment and development strategies in Mutasa, c. 2010-2018 - Chesa, Wonder T. (Midlands State University, 2019)
This study explores and examines development and empowerment strategies initiated on promoting youths in Mutasa District from 2010 to 2018. The investigation aimed on youths in Mutasa District identifying and evaluating the political, economic and social changes brought through youth programmes. Interviews and questionnaires were mostly used during the investigation. The findings indicated that youths were promoted and empowered through donations, funds, awareness campaigns, technical skills from VTCs, business and mining leases, trainings and workshops. Those schemes had achieved its goals to develop and empower the youths in all dimensions. The programme created peaceful political environment in the district than before, provided access to credit facilities, stable market, self-employment creation, inputs accessibility, funding, succeeded in upgrading youth livelihoods through life skills and computing skills. However, personalization of the projects, corruption, lack of unity among youths, unexpected climate changes, poor communication and road networks negatively affected youth programmes in some areas within the district.